2018
DOI: 10.3390/en11020328
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Polymer Solar Cells with Alcohol-Soluble Zirconium(IV) Isopropoxide Cathode Buffer Layer

Abstract: Abstract:Interfacial materials are essential to the performance and stability of polymer solar cells (PSCs). Herein, solution-processed zirconium(IV) isopropoxide (Zr[OCH(CH 3 ) 2 ] 4 , ZrIPO) has been employed as an efficient cathode buffer layer between the Al cathode and photoactive layer. The ZrIPO buffer layer is prepared simply via spin-coating its isopropanol solution on the photoactive layer at room temperature without any post-treatment. When using ZrIPO/Al instead of the traditionally used Ca/Al cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The photosensitive layer was prepared by spin-coating the PBDB-T:ITIC-M chlorobenzene solution (1:1 weight ratio, polymer concentration of 10 mg/mL) with 5% volume ratio of DIO additive on the ITO/PEDOT:PSS and ITO/TOPD substrates at optimized 1,900 rpm for 60 s. Subsequently, the samples were annealed at 100°C for 10 min to obtain the PBDB-T:ITIC-M layer with the thickness of ~100 nm (Bai et al, 2017 ). Finally, the anode of Ca(10 nm)/Al(100 nm) for the control devices or MoO 3 (24 nm)/Al(100 nm) for the inverted PSCs was thermally deposited on the active layer under a base pressure of 5 × 10 −5 Pa (Luo et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The photosensitive layer was prepared by spin-coating the PBDB-T:ITIC-M chlorobenzene solution (1:1 weight ratio, polymer concentration of 10 mg/mL) with 5% volume ratio of DIO additive on the ITO/PEDOT:PSS and ITO/TOPD substrates at optimized 1,900 rpm for 60 s. Subsequently, the samples were annealed at 100°C for 10 min to obtain the PBDB-T:ITIC-M layer with the thickness of ~100 nm (Bai et al, 2017 ). Finally, the anode of Ca(10 nm)/Al(100 nm) for the control devices or MoO 3 (24 nm)/Al(100 nm) for the inverted PSCs was thermally deposited on the active layer under a base pressure of 5 × 10 −5 Pa (Luo et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…When TOPD is used as the CIL to fabricate inverted OSCs, vertical phase separation of the photoactive layer can be realized, which is beneficial for enhancing device efficiency. Tan's group further reported that similar Zr 119 and Hf 120 based coordination complexes can be used as CILs for regular OSCs. For the Hf(ACB1) 4 CIL (Fig.…”
Section: Coordination Complex Based Hybrid Cilsmentioning
confidence: 99%